Европейский Союз и посткоммунистическая Европа: один подход или несколько? - Денджерфилд, М. (Социология: теория, методы, маркетинг, 2008)
The EU member states are now in somewhat reflective mood over future enlargement as the EU grapples with absorbing the current batch of new entrants. The EU has regionalized post-communist Europe into some distinct groups of states, each of which reflects different orders of priority and varied levels of privilege in EU relations. The current EU member states currently hold the cards as far as how deep the relationship between Western Newly Independent States and the EU can go, but ultimately it will be up to the societies and governments of the European Neighborhood Policy countries to determine whether there is meaningful and committed engagement in the European integration process. Thus, in Ukraine Euro-pragmatism has allegedly replaced Euro romantism and there is an urgent need in Euro-realism.